If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1(y + -1Y) = 6 Reorder the terms: X + -1(-1Y + y) = 6 X + (-1Y * -1 + y * -1) = 6 X + (1Y + -1y) = 6 Solving X + 1Y + -1y = 6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1Y' to each side of the equation. X + 1Y + -1Y + -1y = 6 + -1Y Combine like terms: 1Y + -1Y = 0 X + 0 + -1y = 6 + -1Y X + -1y = 6 + -1Y Add 'y' to each side of the equation. X + -1y + y = 6 + -1Y + y Combine like terms: -1y + y = 0 X + 0 = 6 + -1Y + y X = 6 + -1Y + y Simplifying X = 6 + -1Y + y
| 3(3n+1)=9(5n+1)+1 | | x+83+x+63+40=180 | | 5(n-7)=-35+5n | | 0=-4t^2+t+9 | | -7(2T+6)=-14 | | 0.4x-14=20 | | 6x+y=zforx | | 4(F-7)=24 | | 2xy-7y=5 | | -8(S+4)=-12 | | 13s-3=10 | | x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) |